Physical Fitness Analysis of SD Negeri 1 Rejosari Students After the Covid-19 Pandemic - Riyanto, Adi; Lian, Bukman; Junaidi, Ilham Arvan (Yayasan Sembilan Pemuda Indonesia, 2023)
This research was conducted at SD Negeri 1 Rejosari, East OKU Regency, it was found that the physical condition of students at SD Negeri 1 Rejosari, East OKU Regency during the post COVID-19 pandemic, they had not experienced physical decline, as seen from warming up, they had experienced fatigue even though they had not entered the core material of PJOK (Pendidikan Jasmani, Olahraga, dan Kesehatanlearning). So, I as a researcher am very enthusiastic to know the physical fitness of these students. With the state or condition after the pandemic. The purpose of this study was to determine how far the physical fitness level of SDN 1 Rejosari students after the COVID-19 pandemic. The research method is quantitative descriptive research, namely research by giving tests to students, so that physical fitness results are obtained and analysis is carried out. The instrument used in this study was the Indonesian Physical Fitness Test (Tes Kesegaran Jasmani Indonesia). The test items consisted of a 40-meter sprint, a bent elbow hanging test, a 30-second sitting lie test measured using a sit up test, an upright jump and 600-meter run. The data analysis used in this study calculated the physical fitness performance of SDN 1 Rejosari students after the COVID-19 pandemic. The results state that the analysis of the physical fitness of SDN 1 Rejosari students after the COVID-19 pandemic is still lacking.